Deconstructing Cervantes and Dickens in Kathy Acker's Don Quixote and Great Expectations - Gattan Shannan, Dijla (Journal of College of Education, 2020)
Plagiarism and originality are two different forces in any discipline, especially in the academic field. They torment most of the writers, researchers, as well as scholars for they try to avoid plagiarism. Studies shed light upon them. But Kathy Acker turns the scales in her writings, especially in her two novels: Don Quixote and Great Expectations. The purpose   of this paper is what makes an outstanding author as Acker "steal" titles of two famous texts by two famous figures as Cervantes and Dickens, why she "deconstructs" those two novels to "reconstruct" her own.     As long as language is an unstable medium, a literary text has no particular meaning. This means that deconstructionists do not focus on what is said rather than on how it is said. This research concentrates on the way and the purpose behind tackling two novels of male authors by a female novelist who is known on the personal level for her torture of men and her prolonged conflict to achieve her rights (women's rights) in a patriarchal society.      The 1960 is a birth year of deconstructionism, and in 1970 it became an outstanding critical approach to literature. Its major figures are Jacques Derrida, Paul de Man, Roland Barthes and Michel Foucault.  Deconstructionism gives the major role for the reader (reader of any field not only literature) to read the text from his own point of view regardless to writers' intended meaning. For Post-structuralist, there is no absolute truth. Accordingly, there is no one reading, there are as multiple readings and interpretations as there are many readers. This is exactly what happen with Aker's readers. They don't meet Cervantes nor Dickens as the title claim, rather they meet Acker's understanding and employment for the original texts of those male writers.
Keywords: deconstructionist, Kathy Acker, Don Quixote, Great Expectations, Cervantes, Dickens